2014
DOI: 10.17795/semj22326
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and HIV-Related High-Risk Behaviors Among Female Sex Workers

Abstract: Background: Psychological problems have significant associations with HIV-related high-risk behaviors among female sex workers (FSWs). Objectives: The present study aimed to investigate the relationship between mental health and high-risk behaviors among FSWs in Shiraz, Iran. Patients and Methods:This cross-sectional study, conducted from October 2011 to May 2012, used a convenience sampling method to recruit 125 FSWs and 125 control women. After providing informed consent, each participant completed a validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Despite these occupational stressors, mental health of female sex workers (FSWs) is understudied [ 4 ]. The most relevant data on the mental health of this population come from studies assessing the mental health of FSWs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these occupational stressors, mental health of female sex workers (FSWs) is understudied [ 4 ]. The most relevant data on the mental health of this population come from studies assessing the mental health of FSWs.…”
Section: Introductionmentioning
confidence: 99%
“…The most relevant data on the mental health of this population come from studies assessing the mental health of FSWs. Available evidence suggests that FSWs experience worse mental health outcomes than the general public such as high rates of anxiety, depression, posttraumatic stress disorder (PTSD), and psychological distress [ 4 7 ]. These poor mental health outcomes have been associated with experiences of violence, childhood trauma, drug addiction, and the experience of stigma as reported in a review of the literature [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, drug use was a predictor of mental health in the women. The study by Amini-Lari et al showed that the psychosocial status in the female sex workers was worse than that in the control group, and also the drug use had a significant relationship with mental health (31). The study of Hengartner et al aimed at evaluating the mental health in the female sex workers.…”
Section: Discussionmentioning
confidence: 99%